ChemInform Abstract: Piperazine Scaffold: A Remarkable Tool in Generation of Diverse Pharmacological Agents. Issue 45 (November 2015) - Shaquiquzzaman, Mohammad; Verma, Garima; Marella, Akranth; Akhter, Mymoona; Akhtar, Wasim; Khan, Mohemmed Faraz; Tasneem, Sharba; Alam, Mohammad Mumtaz
Abstract Review: 314 refs.